2017
DOI: 10.1007/s12325-017-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing Patterns of Ranibizumab and Aflibercept for the Treatment of Neovascular Age-Related Macular Degeneration: A Retrospective Cohort Study in Australia

Abstract: IntroductionAnti-vascular endothelial growth factor therapy is the standard of care for neovascular age-related macular degeneration (nAMD). The dosage of two licensed agents, ranibizumab and aflibercept, was established through clinical trials; however, it is unclear if either agent is administered as recommended in routine clinical practice. Using pharmacy claims data, we investigated if the dispensing patterns of ranibizumab differ from those of aflibercept 6 and 12 months after treatment initiation.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…On application of pre-specified criteria, data from only a subset of eyes could be included, and we therefore consider the analysis as a pilot study for hypothesis generation. Nonetheless, our attrition rates (~55%) are similar when compared with other cohorts of RWE studies published in the literature, which have reported losses of between 55 and 89% [ 32 34 ]. A larger RWE cohort study with quantification of retinal fluid volume and a longer follow-up period is planned to confirm the robustness of the present results.…”
Section: Discussionsupporting
confidence: 86%
“…On application of pre-specified criteria, data from only a subset of eyes could be included, and we therefore consider the analysis as a pilot study for hypothesis generation. Nonetheless, our attrition rates (~55%) are similar when compared with other cohorts of RWE studies published in the literature, which have reported losses of between 55 and 89% [ 32 34 ]. A larger RWE cohort study with quantification of retinal fluid volume and a longer follow-up period is planned to confirm the robustness of the present results.…”
Section: Discussionsupporting
confidence: 86%
“…Beyond 6 months, approximately one-third of eyes (21–29%) were treated at intervals of 9 to 15 weeks [10]. Dispensing data from regional pharmacies across Australia suggest that licensed anti-VEGFs are dispensed at approximately 5-weekly intervals by Month 6, and at approximately 8-weekly intervals by Month 12 [30]. Although data from these studies are not directly comparable to the present study—the FRB!…”
Section: Discussionmentioning
confidence: 76%
“…Injection and visit frequencies in this study are broadly similar to the FRB! study [10] and dispensing patterns [30] in Australia. Dispensing data can be used as a proxy for injection data, and a recent study found 8.9 units of both ranibizumab and aflibercept were dispensed in the first 12 months of nAMD treatment [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a developing country such as India, under-dosing leading to suboptimal visual outcomes is common. According to a 2017 analysis of a cohort of Australian patients with nAMD, only 40% were still receiving the index treatment 1 year later [ 12 ]. In a study from India, the rate of loss to follow-up was reported to be as high as 51.5% and the most common reasons were non-affordability in 41.4% followed by non-improvement in vision in 28.4% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%